DEVELOPMENT OF DYE SENSITIZED SOLAR CELL (DSSC) WITH NON CONVENTIONAL ELECTROLYTE AND GOLD NANOPARTICLES - Pujiarti, Herlin
Solar cells or photovoltaic cells are devices that convert light energy (photons) into electrical energy. Until now, three generations of solar cells have been developed, namely silicon solar cells, thin-film solar cells, and organic solar cells. From those three generations, organic solar cells are attractive to be studied because the material used in the cells is amorphous and the fabrication process is easy and low cost. Dye-Sensitized Solar Cells (DSSC) is one type of the third-generation of solar cells, which have a structure consisting of (i) TiO2 electrodes superimposed on FTO substrates, (ii) dyes, (iii) electrolytes, (iv) counter electrodes. All components of this solar cell affect the performance of the cells, including the electrolyte materials that have also a specific function to regenerate the photoexcited dyes. The performance, stability, and durability of DSSC are very dependent on the chemical composition and physical properties of the electrolyte. The most widely used electrolyte is a liquid electrolyte based on the redox pair I3-/I- which has several problems in its application, including corrosive properties, especially against metals, volatility, and leakage. In addition, DSSC performance can still be improved because the dye light absorption in DSSC is still not optimum in many cases. A common approach is by introducing a reflective layer. In order to improve the durability and performance of DSSC, this dissertation is focused on (1) developing DSSC with polymer gel electrolytes (PGE) and poly(ionic liquid), (2) and studying the effects of these electrolytes usage to the process of ions and electrons transports in the DSSC, (3) investigating the effect of Au nanoparticle incorporation on the DSSC performance that is related to the plasmonic effect of the nanoparticles. From the experiments conducted in this study, several important results have been obtained. The use of PGE can be optimized by considering the effect of viscosity on PGE penetration in the structure of the TiO2 mesoporous. From the measurement of current vs. characterization voltage (I-V), the efficiency of DSSC with PGE can reach 5,7%, which is close to the reference DSSC with liquid electrolytes in the range of 6,0% in this study. In DSSC with poly(ionic liquid) electrolytes, DSSC efficiency can reach 3,9%, which also approaches the reference DSSC efficiency values which range from 4% for the same sample making series. In poly(ionic liquid) electrolytes that have been successfully made, the imidazole cation is covalently bonded to a siloxane-based crosslinking structure, which naturally has a gel phase. Therefore, in principle, this electrolyte does not require additional solvents like in PGE. The durability test conducted on poly(ionic liquid) also shows that DSSC with poly(ionic liquid) has a longer performance than DSSC with liquid electrolytes. Furthermore, the DSSC study with the incorporation of Au nanoparticle showed that DSSC performance can still be improved by adding AuOA, where the best efficiency of 5,14% can be obtained by the addition of 2,4 wt% Au nanoparticles to the dye. This increase in efficiency is the result of an increase in the conductivity of the TiO2 layer and an increase in photon absorbance as a result of the effects of surface Plasmon Resonance (SPR) generation on Au nanoparticles. However, this addition has an optimum condition when the addition of Au nanoparticle has passed a certain value, this addition actually triggers a charge carrier recombination on the nanoparticle, which reduces the photocurrent.